CHARACTERISTICS OF THE MACULAR MICROVASCULATURE IN IDIOPATHIC EPIRETINAL MEMBRANE PATIENTS WITH AN ECTOPIC INNER FOVEAL LAYER. Issue 4 (April 2023) - Yu, Hwa-Young; Na, Yong-Jin; Lee, Sung-Chul; Lee, Min-Woo
Abstract : The vessel density and perfusion density of the foveal area were significantly higher in patients with ectopic inner foveal layer compared with epiretinal membrane patients without ectopic inner foveal layer, and the foveal avascular zone area and perimeter were significantly lower in patients with ectopic inner foveal layer. Abstract : Purpose: To identify the characteristics of the retinal microvasculature in epiretinal membrane patients with ectopic inner foveal layer (EIFL). Methods: Patients were classified into two groups: those without EIFL (Group 1) and those with EIFL (Group 2). The vessel density (VD), perfusion density (PD), and the foveal avascular zone (FAZ) parameters were compared using optical coherence tomography angiography. Linear regression analysis was performed to identify the optical coherence tomography angiography parameters associated with best-corrected visual acuity. Results: The VD of the central area in Group 1 and Group 2 was 11.6 ± 3.3 and 17.2 ± 2.8 mm −1, respectively ( P < 0.001), the PD of the central area was 21.7 ± 6.2 and 32.0 ± 5.5%, respectively ( P < 0.001), and the FAZ area was 0.24 ± 0.11 and 0.09 ± 0.08 mm 2, respectively ( P < 0.001). Based on the linear regression analysis, the VD of the central area (B = 0.018, P = 0.003), the PD of the central area (B = 0.009, P = 0.004), and FAZ area (B = −0.489, P = 0.013) were significantly associated with best-corrected visual acuity in patients with epiretinal membrane. Conclusion: The VD and PD of the foveal area were significantly higher in patients with EIFL, and the FAZ area was lower in patients with EIFL than in those without EIFL. In addition, the VD and PD of the foveal area were negatively associated with best-corrected visual acuity, and the FAZ area was positively associated with best-corrected visual acuity in patients with epiretinal membrane.